Liability for Nuclear Damage: Perspectives of International Conventions, Indonesian Positive Law, and Islamic Law - Fuadi, Gumilang; Ichsan, Muchammad (UIN Sunan Kalijaga, 2022)
Abstract:Utilization of nuclear energy for nuclear power plants (PLTN/NPP) has great benefits for human life and, at the same time, can also cause an enormous negative impact in the event of an accident. And it is necessary to take responsibility for nuclear losses that might occur. This article examines the liability for nuclear damage from the perspective of international conventions, Indonesian positive law, and Islamic law. This article is a normative-doctrinal study. Using a conceptual, statutory, and comparative approach, this article concludes that there are similarities regarding the principle of liability for nuclear damage in the three legal systems (international conventions, Indonesian positive law, and Islamic law), namely that both adhere to the principle of strict liability, although in Islamic law it is not stated explicitly. On the other hand, some differences between the three legal systems, especially regarding the form of liability and the amount of compensation or compensation that must be given. In international conventions and Indonesian positive law, the responsibility for nuclear damage is attached to the nuclear operator, while in Islamic law, the responsibility for losses is borne by the party carrying out the damage. As for the limit for giving compensation, international conventions and Indonesian positive law have definitively determined it, while in Islamic law, the limit for giving compensation can be determined according to several models, namely: according to mutual agreement (at-taqdīr al-ittifāqi); based on the judge's decision (at-taqdīr al-qadāi), and based on the provisions of the legislature (at-taqdīr asy-syār'i).Abstrak:Pemanfaatan energi nuklir untuk pembangkit listrik tenaga nuklir (PLTN) memiliki manfaat yang besar bagi kehidupan umat manusia dan sekaligus juga dapat menimbulkan dampak negatif yang besar apabila terjadi kecelakaan. Oleh karena itu diperlukan pertanggungjawaban atas kerugian nuklir yang mungkin saja terjadi. Artikel ini mengkaji pertanggungjawaban kerugian nuklir dari sudut pandang konvensi internasional, hukum positif Indonesia, dan hukum Islam. Artikel ini merupakan kajian normatif-doktriner. Menggunakan pendekatan konseptual, perundang-undangan, dan perbandingan, artikel ini menyimpulkan bahwa terdapat persamaan mengenai prinsip pertanggungjawaban kerugian nuklir dalam ketiga sistem hukum tersebut (konvensi internasional, hukum positif Indonesia, dan hukum Islam), yakni sama-sama menganut prinsip tanggung jawab mutlak (strict liability), meskipun dalam hukum Islam tidak dinyatakan secara eksplisit. Di sisi lain, artikel ini juga menemukan adanya beberapa perbedaan di antara ketiga sistem hukum tersebut, terutama mengenai bentuk pertanggungjawaban dan besaran konpensasi atau ganti rugi yang harus diberikan. Dalam konvensi internasional dan hukum positif Indonesia, pertanggungjawaban kerugian nuklir melekat pada operator nuklir, sementara di dalam hukum Islam, pertanggungjawaban kerugian dibebankan kepada pihak yang melakukan tindakan kerusakan. Adapun berkaitan dengan batas pemberian ganti rugi, konvensi internasional dan hukum positif Indonesia telah menetapkannya secara definitif, sementara di dalam hukum Islam, batas pemberian ganti rugi bisa ditetapkan dengan beberapa model, yakni sesuai kesepakatan bersama (at-taqdīr al-ittifāqi); berdasarkan keputusan hakim (at-taqdīr al-qadāi), dan berdasarkan ketetapan pembuat undang-undang (al-taqdīr al-syār 'i).Keywords: Liability for nuclear damage; international conventions; Indonesian positive law; Islamic law